D11 Expression Analysis Of Genes Coding For Pet Ligands In HD Mouse Models. (17th September 2014) - Osborne, GF; Salsbury, G; Ali, NS; Franklin, S A; Goodwin, D; Landwehrmeyer, GB; Park, L; Munoz-Sanjuan, I; Bates, GP
Abstract : Background: The ability to monitor clinical trials in Huntington's disease (HD) patients with pharmacodynamic read outs will be essential, and PET ligands that give altered signals in HD patient brains are being considered for use in monitoring huntingtin-lowering strategies. However, there are many PET ligands in clinical use that have never been assessed in Huntington's disease (HD) patient brains. As a first step in the investigation as to which of these ligands might provide useful biomarkers for HD, we have determined whether the transcript levels of the genes encoding the ligands are dysregulated in the brains of HD mouse models. Methods/techniques: We measured the level of expression of genes encoding 13 PET ligands in the striatum and cortex of R6/2 mice with repeat expansions of 200Q and 90Q as well as the zQ175 knock-in mouse model at a range of ages. Results/outcome: Significant dysregulation was detected in symptomatic R6/2 with 200Q as compared to wild-type mice for most of the PET ligand genes. The genes that were most dysregulated in the R6/2 mice with 200Q were then analysed in the cortex of R6/2 mice with 90Q and found to be dysregulated at a pre-symptomatic stage. The extent of dysregulation was next examined in the zQ175 knock-in mouse line and gene expression was compared in wild-type, heterozygous and homozygous mice at 2, 4, 6 and 8 months. The most striking differences were observed between wild-type and homozygous mice. In some instances genes encoding several of the PET ligands were dysregulated as early as 4–6 months of age, prior to onset of symptoms. Conclusions: These results suggest that investigation of some of these novel PET ligands in HD patients could be highly informative. This work was funded by the CHDI Foundation.